ஹரணியின் சிறுகதைகளில் வாழ்வியல் சிந்தனைகள் / Life Thoughts in Harani's Short Stories - செ. மோகனசுந்தரி / S. Mohanasunthari; முனைவர் நா.சிவாஜிகபிலன்/Dr. N. Sivajikapilan (Chenkaantal)
Literature is a mirror that reflects life. The concepts of literature do a great job of guiding an individual. They give life-enhancing ideas to the perplexed individual. Living life in an orderly manner is considered to be a pleasant practice of living. Morality is a virtue. If one lives by virtue, the individual can live a better life. The morality of the individual is the basic reason for the development of society. In this way, literature is created to clarify the human mind by stating what should be done and what should not be done in life. The word ethics refers to the meaning such as morals, didactic, ethical principles, life ethics, benevolent characteristics, etc. Among these, the term "life ethics" or "life ideas" has gained widespread acceptance and has been established in the case of social rejuvenation. In this way, the purpose of this article is to explore the concepts of life such as culture, family, friendship, self-reliance, pride, and humanity in the short stories of Harini.